PENERAPAN TEORI BELAJAR VAN HIELE PADA MATERI SEGIEMPAT UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA KELAS VII SMP - Magrib (Jurnal Pemikiran dan Penelitian Pendidikan Matematika (JP3M), 2018)
This study applies Van Hiele's learning theory to quadrilateral to improve activities and student learning achievements carried out in three cycles. Student learning achievement data obtained through learning evaluation, student learning activity data obtained through observation sheets of student learning activities and teacher activity data obtained through teacher activity observation sheets. The results of the first cycle of research included scores of student learning activities on average at 7.33 which were categorized as less active and the results of student evaluations with an average value of 73.3 with learning completeness of 77%. While the results of the second cycle of research include scores of student learning activities on average by 10.67 which are in the active category and the results of student evaluations with an average value of 63.8 with learning completeness of 60.4%. Then the results of the third cycle of research include scores of student learning activities on average by 13.33 which are in the active category and the results of student evaluations with an average value of 76.9 with learning completeness of 79.2%. Based on the results of the research and the achievement of work indicators, it can be concluded that the application of Van Hiele's learning theory to quadrilateral material can increase the activity and learning achievement of VII grade students of SMP.